2020
DOI: 10.1007/978-3-030-57537-3_7
|View full text |Cite
|
Sign up to set email alerts
|

Climate Resilience in Urban Informal Settlements: Towards a Transformative Upgrading Agenda

Abstract: Informal settlements are on the frontline in the battle against climate change. Home to one billion people, their infrastructure deprivations pose challenges for the health and resilience of communities and ecosystems. Upgrading of informal settlements can improve urban services and infrastructure, strengthen tenure security, and empower local communities. This chapter examines the conceptual and practice relationships between climate resilience and in-situ upgrading. It critiques prevailing approaches, which … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 61 publications
0
8
0
2
Order By: Relevance
“…Among growing concerns with floods and other environmental hazards, citizen science has emerged as a promising approach for involving communities in disaster risk management (Cooper et al, 2021). Investigating how community members can contribute to more inclusive risk management practices is particularly important in the context of informal settlements, which are expected to be disproportionately affected by the impacts of climate change (French et al, 2020;Hoegh-Guldberg et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Among growing concerns with floods and other environmental hazards, citizen science has emerged as a promising approach for involving communities in disaster risk management (Cooper et al, 2021). Investigating how community members can contribute to more inclusive risk management practices is particularly important in the context of informal settlements, which are expected to be disproportionately affected by the impacts of climate change (French et al, 2020;Hoegh-Guldberg et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Characterised by insecure land tenure, lack of access to infrastructure and non-conformity with regulatory frameworks (UN Habitat III, 2017), informal settlements are also expected to be disproportionately impacted by climate change due to their rapid urban growth over areas at high risk from extreme weather (Bettini et al, 2017;Chandler, 2019;French et al, 2020;Revi et al, 2014). Some works have critiqued the social and political implications of the application of traditional risk management in informal settlements (French et al, 2020;Sandoval & Sarmiento, 2020;Yarina, 2018), which have historically been severely affected by floods and tropical cyclones. Emerging as an alternative, community-based approaches consider communities not as clients or external consultants, but as central agents in risk identification, monitoring and communication (Shaw, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Some studies have also indicated that there are vast environmental problems associated with informal settlements and low-income houses related to the location, drainage, and waste disposal. These studies argue that several low-income houses, including informal settlements, are located in unplanned land (French et al 2021). For example, infrastructure such as water supply pipelines and electricity poles are not placed in a controlled way and hence they can trigger environmental problems.…”
Section: Environmental Impact and Contaminationmentioning
confidence: 99%
“…En particular, la mayoría de los asentamientos humanos informales, situados en áreas urbanas con valores ecosistémicos, constituyen espacios geográficos precarizados en los cuales generan nuevos modos de vida y, al mismo tiempo, modifican los entornos naturales para la satisfacción de sus necesidades. Los asentamientos informales (ai), al encontrarse al margen de los sistemas oficiales de regulación y planificación urbana, además de carecer de servicios básicos, infraestructura de vivienda y seguridad de la tenencia de la tierra, plantean desafíos ambientales para las personas y los ecosistemas (French et al, 2021).…”
Section: Introductionunclassified
“…En virtud de la necesidad de generar modelos de gestión de riesgos aplicados con fines socioespaciales específicos (French et al, 2021), el propio concepto de resiliencia de comunidades ha sido aplicado como una medida de la capacidad sostenida de cierta comunidad para utilizar los recursos disponibles para responder, resistir y recuperarse de situaciones adversas, como tsunamis, deslaves, etc. (Abir et al, 2016).…”
Section: Introductionunclassified